The consciousness of Turkiye in Malaysia Ottoman history in Malaysian secondary history textbooks (1989-2022) - Mohd Noor Merican, Ahmad Murad; Akgun, Tayfun (IIUM Press, 2023)
This article explores the teaching of Ottoman history and the image of the Ottomans through a close and critical reading of Malaysian secondary history textbooks used between 1989 and 2022. It argues that Malaysian secondary history textbooks focus mainly on the political and military aspects of sixteenth-century Ottoman history. They do not, consciously or subconsciously, make detailed reference to political and socio-economic turning points in nineteenth-century Ottoman history. Sejarah Tingkatan 2 (History: Form 2), one of the history textbooks examined in the article, exceptionally discusses the impact of Ottoman pan-Islamism and Turkish nationalism on the political and religious thought of the Malays. Nonetheless, history textbooks published after the 2000s have not touched on these important issues. In history textbooks, the Ottoman Empire is regarded as one of the significant states of the Islamic world; therefore, Ottoman history is analyzed within the framework of Islamic history and Islamic civilization. The portrayal of Ottomans is positive and favourable. There are no distortions, biases, or stereotypes concerning Ottoman history in Malaysian secondary history textbooks.